2014
DOI: 10.1007/s11224-014-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and quantum mechanical studies on biflavonoid structures as BACE-1 inhibitors

Abstract: Beta-site amyloid precursor protein cleaving enzyme (BACE-1) is a well-known therapeutic target for Alzheimer disease (AD) due to its characteristic role in the pathogenesis of AD. Numerous researches have been focused on the design and development of potent peptidic and nonpeptidic BACE-1 inhibitors. In the present contribution, a series of experimentally validated biflavonoid BACE-1 inhibitors (1-21) were subjected to our structure-based molecular modeling studies. Binding modes were elucidated through molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…As shown in Figure 8, the biuret moiety in the majority of the selected compounds participates in hydrogen bonding with Asp 25, Gly 27, and Ile 50. The hydrogen bonding of Asp 25 with different inhibitors has been previously reported 67 . In summary, docking results revealed that all of the selected compounds could occupy an HIV‐1 protease active site.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…As shown in Figure 8, the biuret moiety in the majority of the selected compounds participates in hydrogen bonding with Asp 25, Gly 27, and Ile 50. The hydrogen bonding of Asp 25 with different inhibitors has been previously reported 67 . In summary, docking results revealed that all of the selected compounds could occupy an HIV‐1 protease active site.…”
Section: Resultssupporting
confidence: 55%
“…The HIV‐1 protease is a homodimeric protease including two identical 99‐residue monomers. Each monomer consists of the conserved triads (Asp‐Thr‐Gly) in positions of 25–27 and 25′–27′, that aspartate amino acids do all of the catalytic activities 67 . All the selected compounds were successfully docked into the corresponding active site of HIV‐1 protease (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Maximum generation was set as 27 000 with 5 000 000 number of energy evaluations in 200 genetic algorithm runs, 0.02 and 0.8 for gene mutation rate and crossover rate respectively. Final cluster analysis of similar conformations was applied with the root mean square deviation (RMSD) tolerance of 2 [12]. Different conformers with total number of 150 were produced following the genetic algorithm.…”
Section: Molecular Docking Preparation and MD Simulationmentioning
confidence: 99%
“…Razzaghi-Asl et al [143] reported the results of a theoretical structure-based molecular modeling study of a therapeutic target for Alzheimer's disease, a beta-site amyloid precursor protein-cleaving enzyme, which was previously experimentally validated. A reasonable correlation (R 2 = 0.61) was calculated between the theoretical and experimental binding affinities.…”
Section: Issuementioning
confidence: 99%